Faktor – Faktor Yang Menyebabkan Kegagalan Pemberian Asi Eksklusif di Kelurahan Tomuan Kecamatan Siantar Timur Kabupaten Simalungun Tahun 2023 - Merita Elferida; Sri Rezeki; Amelia Erawaty Siregar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Mothers who do not exclusively breastfeed their children will have a negative impact on public health, causing upper respiratory tract infections (ARI), diarrhea, the baby's immune system, affecting the level of intelligence of the brain after adulthood and can trigger allergies, obesity and disease. intestines in premature babies and can also put the mother at risk of breast cancer. The aim of the research is to determine the factors that cause the failure of exclusive breastfeeding in Tomuan Village, East Siantar District, Simalungun Regency in 2023.The research design used was cross sectional and analytical in nature. The population in this study were all mothers with babies 6-9 months living in Tomuan Village, totaling 208 people using accidental sampling technique.The results of the research on the relationship between knowledge and exclusive breastfeeding show a p value of 0.007, the relationship between education and failure to provide exclusive breastfeeding shows a p value of 0.000, the relationship between work and failure to provide exclusive breastfeeding shows a p value of 0.000.For health workers in Tomuan Village, it is hoped that they will provide more services and increase access that supports the exclusive breastfeeding movement for mothers of babies, such as lactation rooms in every public place and monitoring the implementation of breastfeeding programs for working mothers in particular.